"إنعكاسات تقلبات أسعار النفط على ميزان المدفوعات الجزائري دراسة حالة الجزائر 2000 – 2016 " - العايب, هيثم; تجاني, محمد الصالح; بن عمر, محمد الصالح (university of eloued, 2018)
This study aims to examine the relationship between the fluctuations in oil prices and components of the Algerian balance of payments, and on the basis that the national economy is a first class economy. Oil exports in this economy occupy about 98%. Therefore, the oil sector is considered one of the main pillars on which it relies As a result of this excessive dependence, the national economy has been severely affected by the fluctuation in oil prices, which has caused great fluctuations in the stability of the national economy, whether internally or externally. At the end of this study, the impact of fluctuations in oil prices on the balance of payments elements was realized. The balance of payments elements were affected by fluctuations in oil prices from the trade balance on the one side and foreign exchange reserve and capital account on the other hand. Oil.
مذكرة ماستر تجارة دولية
Keywords: ميزان المدفوعات الجزائري، اسعار النفط ، الميزان التجاري الجزائري